2021
DOI: 10.5194/acp-21-4779-2021
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Emission factors, chemical composition, and morphology of particles emitted from Euro 5 diesel and gasoline light-duty vehicles during transient cycles

Abstract: Abstract. Changes in engine technologies and after-treatment devices can profoundly alter the chemical composition of the emitted pollutants. To investigate these effects, we characterized the emitted particles' chemical composition of three diesel and four gasoline Euro 5 light-duty vehicles tested at a chassis dynamometer facility. The dominant emitted species was black carbon (BC) with emission factors (EFs) varying from 0.2 to 7.1 mg km−1 for direct-injection gasoline (GDI) vehicles, from 0.02 to 0.14 mg k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 120 publications
(170 reference statements)
1
9
0
Order By: Relevance
“…This implies that the pollution in the region is primarily vehicle emission. Similarly, previously studies have shown that the metal and heavy metals Fe, Cr, Cu, and S are the main pollutants in urban street dust [31,33,34]. It can be confirmed that the PM10 in Bangkok, Thailand has a wide range of physical and chemical characteristics including structure, shape, size, and chemical composition.…”
Section: Morphology and Chemical Composition Of Pm10supporting
confidence: 67%
“…This implies that the pollution in the region is primarily vehicle emission. Similarly, previously studies have shown that the metal and heavy metals Fe, Cr, Cu, and S are the main pollutants in urban street dust [31,33,34]. It can be confirmed that the PM10 in Bangkok, Thailand has a wide range of physical and chemical characteristics including structure, shape, size, and chemical composition.…”
Section: Morphology and Chemical Composition Of Pm10supporting
confidence: 67%
“…Unburned hydrocarbons that were not oxidized at the TWC during the cold start are a possibility. Many studies have measured PAHs (polycyclic aromatic hydrocarbons) from GDIs [70,71], in particular during cold start [72]. The boiling point of PAHs is <600 • C [73].…”
Section: Discussionmentioning
confidence: 99%
“…Different after-treatment technologies (e.g., DOC + DPF and SCR) are adopted by different manufacturers to limit pollutant emissions in compliance with the standard. Previous studies have demonstrated that changes in engine technologies and after-treatment devices can profoundly alter the chemical composition of the emitted pollutants, 70 resulting in increased emission of unregulated reactive organics and TOR. Therefore, further studies should investigate the TOR from China VI vehicles with different combinations of after-treatment technologies to evaluate whether the newest emission standard is conducive to reducing OH reactivity and mitigating secondary pollution in the atmosphere.…”
Section: ■ Implicationsmentioning
confidence: 99%